Vozes do chão em vasto mundo: uma análise da obra neorregionalista de Maria Valéria Rezende à luz da geografia humanista cultural - MENDES, Danielle Gomes (2021)
This research aims to analyze the work Vasto mundo (2001), by Brazilian author Maria Valéria Rezende, in the light of Humanistic Cultural Geography, with a phenomenological bias. The story revolves around a small village called Farinhada, located in the Northeast of Brazil. Residents have a strong connection to their homeland and sometimes find it difficult to adapt to other places, especially in the urban context. It is the very soil of the Farinhada that reveals the movements of these people to us, as well as examining the interior of each man and woman who passes or inhabits them. The dry land gives maternal affection to its residents and establishes an interdependent relationship. Rezende builds in her work a generous Northeast, although punished by the dry climate and poverty, on the other hand, the author weaves her backlands in the hope, joy and culture of the people of the Northeast. The analysis deals with an interdisciplinary reading, in which a dialogue is established between literary criticism, Humanistic Cultural Geography, based on phenomenology, and studies that dialogue with the themes of belonging. The concepts of: space; Put, put; Home; topophilia, topophobia; crowd; amplitude; place-without-place; rooting and some feelings related to the spatial issues experienced by the characters of the work, such as "fear" and "hope". For such a discussion, the theoretical contribution of Humanist Cultural Geography is necessary, especially by geographers Eric Dardel, Yi-Fu Tuan and Edward Relph. The work shows traces of a regionalist tradition seen from the perspective of the contemporary, therefore, to observe the thematic referent, authors from other areas will also be referenced. From literary criticism, the following stand out: Luís Bueno (2006); Alfredo Bosi (2017); Antônio Candido (2016), Massaud Moíses (2012); Antonio Dimas (2014); Eduardo Coutinho (2019); and others. The contributions of historians and anthropologists show the work of: Durval Albuquerque Júnior (2011); Lillian Schwartz (2012); Gilberto Freyre (1996); Lévi-Strauss (1976); Anthony Giddens (2013); and memory theorists: Maurice Halbwacks (2003) and Michel Pollak (1992).